2018
DOI: 10.1002/etc.4165
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of a deep‐sea fish species (Anoplopoma fimbria) to oil‐associated aromatic compounds, dispersant, and Alaskan North Slope crude oil

Abstract: A predominant concern following oil spills is toxicity to aquatic organisms. However, few data are available on effects in deep-sea cold water fishes. The present study had 3 major objectives. The first was to investigate the relative sensitivity of the deep-sea species Anoplopoma fimbria (sablefish) to acute effects of 3 aromatic compounds (toluene, 2-methylnaphthalene, and phenanthrene), dispersant alone, and chemically enhanced water accommodated fractions (CEWAFs) of Alaskan North Slope crude oil. The seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…7). Although these CTLBBs are calculated from one hydrocarbon and should therefore be interpreted as preliminary, the CTLBB Sublethal ( ) and CTLBB Lethal ( ) for these scleractinian coral species indicate that they are comparatively more resilient to narcotic chemical exposure compared to other species for which similar data is available 18,34,35 . The CTLBB Sublethal for the most sensitive species tested here, A. cervicornis, falls at the 82nd percentile.…”
Section: Resultsmentioning
confidence: 99%
“…7). Although these CTLBBs are calculated from one hydrocarbon and should therefore be interpreted as preliminary, the CTLBB Sublethal ( ) and CTLBB Lethal ( ) for these scleractinian coral species indicate that they are comparatively more resilient to narcotic chemical exposure compared to other species for which similar data is available 18,34,35 . The CTLBB Sublethal for the most sensitive species tested here, A. cervicornis, falls at the 82nd percentile.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, little data are available on biological responses of species that inhabit deepwater environments. Although some evidence suggests that their sensitivity is comparable to that of most traditionally tested species (Frometa et al 2017;Knap et al 2017;McConville et al 2018), confirmation of their relative sensitivity would be potentially useful. In the present study, models were used to fill data gaps and generate provisional HC5s for several dispersants.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being a commonly considered response tool, in the United States dispersants have been used approximately 20 times since 1969 (National Oceanic and Atmospheric Administration 2018). Although it is generally well accepted that the drivers of aquatic toxicity in the water column following the use of newgeneration dispersants are the dissolved fractions of the treated oil (National Research Council 2005) and although recent laboratory studies have further demonstrated that dispersants are less toxic than the tested oils (e.g., Hemmer et al 2011;Barron et al 2013;Claireaux et al 2013;McConville et al 2018), concerns persist about their toxicity. This exceptional use of dispersants raised concerns among the public and many scientists about the potential toxicity of these substances to water column organisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to emphasize that since the concentration of individual PAHs varies widely across different crude oils (and weathering states) and given different investigators often quantitate an inconsistent target list of individual PAHs to characterize oil toxicity test exposures, the ratio of TUs associated with measured PAHs to unresolved dissolved oil components is expected to diverge across oil toxicity studies. This conclusion is supported by the recent modeling analysis provided by McConville et al (2018) who investigated the acute toxicity of chemically dispersed Alaska North Slope Oil to sablefish. These investigators found that a suite of 38 individual PAHs used to quantify total PAH exposures in CEWAF treatments represented 20% of ∑TUs that were predicted based on 2d-GC analysis of the test oil.…”
Section: Comparing Predicted Tus For Whole Oil Versus Total Pahmentioning
confidence: 55%